Analisis Pengaruh Variabel Makro yang Mempengaruhi Nilai Tukar Rupiah - Hesniati; Ayu Fauzia Rahmah; Teddy Ricardo; Jessica Angelina; Wendy; Laurentcia Longli (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Changes in economic conditions both domestically and internationally can have an impact on exchange rate stability. In this case, fluctuations in exchange rates are not only influenced by the law of supply and demand for foreign exchange in the market, but changes in market expectations also affect it. The research was conducted to determine the effect of several macro variables on the rupiah exchange rate. This research was conducted using multiple linear regression analysis method. The results of the study indicate that the macro variables that affect the rupiah exchange rate such as money supply, foreign exchange reserves, inflation and interest rates are different but significant.